Foraging ecology of insectivorous bats in Universiti Malaysia Sarawak (UNIMAS) campus - Anum Fairuz, binti Ahmad Mazlan (Universiti Malaysia Sarawak, (UNIMAS), 2006)
This study describes the feeding ecology of insectivorous bats under natural condition at light source in Universiti Malaysia Sarawak (Unimas) campus. Throughout 18 nights of sampling that was conducted from October 2005 to February 2006, only two species of insectivorous bats namely Kerivoula papil/osa and K. pellucida, were observed foraging at the light sources. The activity of insectivorous bats foraging at the study sites were detected using Mini-3 bat detector while the insect activity was determined by the number of insects collected at each sampling site using light sheet trap. The result shows that insectivorous bat activity was positively correlated with insect activity (Pearson's correlation coefficient at 0.05 level) and insectivorous bat feeds on insects regardless of their sizes.